Validation of Serological Methods for COVID-19 and Retrospective Screening of Health Employees and Visitors to the São Paulo University Hospital, Brazil - Andreata-Santos, Robert; Machado, Rafael Rahal Guaragna; Alves, Rúbens Prince dos Santos; Sales, Natiely Silva; Soares, Camila Pereira; Rodrigues, Karine Bitencourt; Silva, Mariângela Oliveira; Favaro, Marianna Teixeira de Pinho; Rodrigues-Jesus, Mônica Josiane; Yamamoto, Márcio Massao; Andrade, Juliana Bannwart de; Fock, Ricardo Ambrósio; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Reliable serological tests for the detection of SARS-CoV-2 antibodies among infected or vaccinated individuals are important for epidemiological and clinical studies. Low-cost approaches easily adaptable to high throughput screenings, such as Enzyme-Linked Immunosorbent Assays (ELISA) or electrochemiluminescence immunoassay (ECLIA), can be readily validated using different SARS-CoV-2 antigens. A total of 1,119 serum samples collected between March and July of 2020 from health employees and visitors to the University Hospital at the University of São Paulo were screened with the Elecsys® Anti-SARS-CoV-2 immunoassay (Elecsys) (Roche Diagnostics) and three in-house ELISAs that are based on different antigens: the Nucleoprotein (N-ELISA), the Receptor Binding Domain (RBD-ELISA), and a portion of the S1 protein (ΔS1-ELISA). Virus neutralization test (CPE-VNT) was used as the gold standard to validate the serological assays. We observed high sensitivity and specificity values with the Elecsys (96.92% and 98.78%, respectively) and N-ELISA (93.94% and 94.40%, respectively), compared with RBD-ELISA (90.91% sensitivity and 88.80% specificity) and the ΔS1-ELISA (77.27% sensitivity and 76% specificity). The Elecsys® proved to be a reliable SARS-CoV-2 serological test. Similarly, the recombinant SARS-CoV-2 N protein displayed good performance in the ELISA tests. The availability of reliable diagnostic tests is critical for the precise determination of infection rates, particularly in countries with high SARS-CoV-2 infection rates, such as Brazil. Collectively, our results indicate that the development and validation of new serological tests based on recombinant proteins may provide new alternatives for the SARS-CoV-2 diagnostic market.